Discovery of metastases in thyroid cancer and "benign metastasizing goiter": a historical note - Kushchayev, Sergiy; Kushchayeva, Yevgeniya; Glushko, Tetiana; Pestun, Iryna; Teytelboym, Oleg (Frontiers in Endocrinology, 2024)
At the beginning of the eighteenth century, most physicians recognized cancer as an aggressive process that gradually spreads, leading to cachexia and death. Thyroid malignancies had long been underestimated because the majority of the population of West Europe suffered from diffuse goiters that masked malignant processes in the neck. Moreover, the life expectancy at that time was very low (about 37-40 years), so the majority of people died of other causes before metastatic thyroid cancer could develop and manifest. Nevertheless, in 1817, French dermatologist Jean Louis Alibert described the first case of a malignant tumor involving the thyroid gland. From the 1820s the number of case reports describing thyroid cancer increased. Even though Jean Claude Recamier described metastases in 1829, secondary lesions on various organs in patients with thyroid malignancies were not themselves considered malignant until 1876.